2022
DOI: 10.3389/fmars.2022.1037017
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an ultrafiltration membrane for the removal of fish viruses and bacteria in aquaculture water

Abstract: Ultrafiltration (UF) membranes are used to successfully remove waterborne virus and bacteria from wastewater and drinking water. However, UF membrane application in aquaculture water treatment is limited. In this study we evaluate the performance of a capillary polyethersulfone UF membrane to remove two benchmark waterborne fish pathogens: i) the infectious pancreatic necrosis virus - IPNV, which is an unenveloped icosahedral virus, and ii) the bacterium Aeromonas salmonicida, which is a Gram-negative, faculta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 19 publications
(18 reference statements)
0
0
0
Order By: Relevance
“…A study by Hembach et al reported a decrease of an average of 5 log units in the number of both facultative bacteria and antibiotic resistance genes in the water tested, which originated from a wastewater treatment plant [47]. An in-vitro study by Mota et al, indicated that the usage of ultrafiltration membranes effectively removed fish pathogens, including viruses, which may find wider application in aquaculture [48]. These results confirm the high effectiveness of the use of ultrafiltration membranes.…”
Section: Discussionmentioning
confidence: 82%
“…A study by Hembach et al reported a decrease of an average of 5 log units in the number of both facultative bacteria and antibiotic resistance genes in the water tested, which originated from a wastewater treatment plant [47]. An in-vitro study by Mota et al, indicated that the usage of ultrafiltration membranes effectively removed fish pathogens, including viruses, which may find wider application in aquaculture [48]. These results confirm the high effectiveness of the use of ultrafiltration membranes.…”
Section: Discussionmentioning
confidence: 82%